El proyecto fichteano de un derecho penal independiente de la ética - Arrese, Héctor (2011)
"The Fitchean Project of a Penal Right Independent from Ethics". in this paper I intend to examine the Fitchean Project of building a theory of right independent from ethics, especially in the sphere of penal right. I consider that the ideas of atonement for pure and applied right are different. This difference responds to the psychological and moral presuppositions of each and puts the internal consistency of the theory into checkmate.